Improving speech-to-text for the Indonesian language using a modified transformer - Atika, Ratna; Dwijayanti, Suci; Suprapto, Bhakti Yudho (Eastern-European Journal of Enterprise Technologies, 2026)
The object of this study is a transformer-based ASR architecture trained using an Indonesian speech dataset consisting of audio recordings and corresponding transcripts. This study examines the development of an Automatic Speech Recognition (ASR) system for Indonesian, which is still classified as a low-resource language, particularly in terms of dataset availability and model performance. The problem addressed in this study is the limited performance of the standard transformer model in accurately recognizing Indonesian speech. To overcome this limitation, an encoder modification integrating convolutional and vision transformer (ViT) blocks was proposed and compared with the baseline model. The data were preprocessed through 16 kHz mono audio conversion, silence segmentation, pre-emphasis filtering, log-Mel spectrogram extraction, normalization, and subword tokenization using SentencePiece with byte pair encoding (BPE). The dataset was divided into training, validation, and testing sets with a ratio of 80:10:10, comprising 63,952, 7,994, and 7,994 samples, respectively. Model generalization was improved using the SpecAugment data augmentation technique. The experimental results show that the standard model achieves a word error rate (WER) of 0.162 and a character error rate (CER) of 0.121, while the modified model reduces the WER to 0.158 and the CER to 0.118. The significance of this finding lies in the improved feature representation produced by the modified encoder, where the convolutional block captures local acoustic patterns and the ViT block enhances global context modeling on the spectrogram. This complementary mechanism explains the reduction in errors at the word level, which is crucial for a reliable speech-to-text system. Therefore, the proposed model can be applied to real-time two-way communication in service robot applications